2015
DOI: 10.1097/bot.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Treatment on Mortality After Acetabular Fracture in the Elderly

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 24 publications
2
44
1
3
Order By: Relevance
“…We found no differences between the operative and the non-operative group in regards to all-cause 1year-mortality. This finding is consistent with a previous studies that conclude that there is no difference in 1- year mortality between operative and non-operative management, once comorbidities are taken into account [4,10]. Existing literature states 1-year mortality rates of 16 to 35% for non-operative treatment [10,[12][13][14] and of 4 to 21% for operative treatment [10,12,13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found no differences between the operative and the non-operative group in regards to all-cause 1year-mortality. This finding is consistent with a previous studies that conclude that there is no difference in 1- year mortality between operative and non-operative management, once comorbidities are taken into account [4,10]. Existing literature states 1-year mortality rates of 16 to 35% for non-operative treatment [10,[12][13][14] and of 4 to 21% for operative treatment [10,12,13].…”
Section: Discussionsupporting
confidence: 91%
“…Whereas the main mechanism of injury for younger patients is high-energy-trauma, the majority of acetabular fractures in the elderly are a result of a fall from standing height [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a selection bias, with published series of surgically managed elderly acetabular fractures being inherently healthier than those of neck of femur fractures. Gary et al attempted to look at mortality with a retrospective review of cases from 3 level 1 trauma centres, cases being stratified into nonoperative, percutaneous fixation, open reduction and internal fixation, or acute total hip replacement [ 14 ]. Although they found no significant improvement of surgical over nonoperative management (and thus concluded that decisions regarding surgical management of these cases should not be based on concern over the mortality of nonoperative management) their final adjusted mortality by treatment graph shows a clinically important if not statistically significant advantage to immediate hip arthroplasty over all other forms of management.…”
Section: Discussionmentioning
confidence: 99%
“…In young patients, better reduction is associated with a better clinical outcome and a lower rate of secondary osteoarthritis [3,[8][9][10][11][12]. Many studies identified higher age as a negative predictor regarding reduction, mortality and complications, though [1,[13][14][15]. Percutaneous screw fixation of acetabulum fractures has the advantage of less invasive approaches and lower blood loss and, hence, seems to be a potential alternative for geriatric patients [15][16][17].…”
Section: Introductionmentioning
confidence: 99%